Transition-Metal-Catalyzed Asymmetric Allylation of Carbonyl Compounds with Unsaturated Hydrocarbons - Wang, Pu-Sheng; Shen, Meng-Lan; Gong, Liu-Zhu (Synthesis, 2018)
The asymmetric allylation of carbonyl compounds is an important process for the formation of carbon–carbon bonds, generating optically active homoallylic alcohols that are versatile building blocks with widespread applications in organic synthesis. The use of readily available unsaturated hydrocarbons as allylating reagents in the transition-metal-catalyzed asymmetric allylation has received increasing interest as either a step- or an atom-economy alternative. This review summarizes transition-metal-catalyzed enantioselective allylations on the basis of the ‘indirect’ and ‘direct’ use of simple unsaturated hydrocarbons (include dienes, allenes, alkynes, and alkenes) as allylating reagents, with emphasis on highlighting conceptually novel reactions.1 Introduction2 ‘Indirect’ Use of Unsaturated Hydrocarbons in Asymmetric Allylation of Carbonyl Compounds2.1 Enantioselective Allylation with 1,3-Dienes2.2 Enantioselective Allylation with Allenes2.3 Enantioselective Allylation with Alkenes3 ‘Direct’ Use of Unsaturated Hydrocarbons in Asymmetric Allylation of Carbonyl Compounds3.1 Enantioselective Allylation with 1,3-Dienes3.2 Enantioselective Allylation with Allenes3.3 Enantioselective Allylation with Alkynes3.4 Enantioselective Allylation with Alkenes4 Conclusions
Keywords: asymmetric catalysis; allylation; homoallylic alcohol; unsaturated hydrocarbon; transition-metal catalysis